Novel SMAD3 variant identified in a patient with familial aortopathy modeled using a zebrafish embryo assay - Sheppard, Mary B.; Smith, Jeffrey D.; Bergmann, Lisa L.; Famulski, Jakub K. (Frontiers in Cardiovascular Medicine, 2023)
In human, pathogenic variants in smad3 are one cause of familial aortopathy. We describe a novel SMAD3 variant of unknown significance (VUS), V244F, in a patient who presented with aortic root dilation, right coronary artery ectasia, abdominal aortic aneurysm, right vertebral artery atresia, and cavernoma. Determination of variant pathogenicity impacted multiple aspects of the patient’s care, including the most appropriate surgical threshold for which to recommend a valve-sparing aortic root replacement. To determine whether the newly identified SMAD3 variant, and whether SMAD3 induced aortopathy in general, can be assayed in a zebrafish embryo model, we injected smad3a mRNA into Tg[kdrl:mCherry] zebrafish embryos. By measuring the size of the dorsal aorta at 48hpf we found a correlation between pathogenic SMAD3 variants and increased dorsal aortic diameter. The newly identified V244F variant increased dorsal aortic diameter (p<0.0001) similar to that of the pathogenic control variant T261I (p<0.05). In addition, we examined several previously identified variants of uncertain significance and found P124T (p<0.018), L296P (p<0.0009) and A349P (p<0.0001) to behave like T261I. These results demonstrate that the zebrafish embryo assay was successful in validating known pathogenic variants, classifying our newly identified variant V244F as likely pathogenic, and classifying previously identified variants P124T, L296P and A349P as likely pathogenic. Overall, our findings identify a novel SMAD3 variant that is likely pathogenic as well as offer a new mechanism to model SMAD3 VUSs in vivo.